Specific immunotherapy for allergic diseases - Ariyanto Harsono (Paediatrica Indonesiana, 2005)
Specific allergen immunotherapy (SIT)involves the administration of allergenextracts to modify or abolish symptomsassociated with atopic allergy. The process isspecific, in that the treatment is targeted at thoseallergens recognized by the patient and physician asresponsible for symptoms. A decision to use SITtherefore demands a careful assessment of the patient’scondition and the role of allergic triggers.Immunotherapy was first developed at St Mary’sHospital, London at the end of the 19th century, andmany of the basic principles remain valid today.